Persepsi Siswa Kelas XI terhadap Metode Pembelajaran yang Variatif dalam Mata Pelajaran Al-Qur’an Hadist - Rizqiyatun Nida; Azizah Nur Fadilah; Bagir Muhammad; Bq Widiya S. Wati; Fathir M. Haikal; Muhammad Reivei Saubari (JOEAI (Journal of Education and Instruction), 2026)
This study aims to determine the perceptions of Grade XI students regarding the use of varied teaching methods in the Al-Qur’an Hadist subject at MA Negeri Kotabaru, as well as to identify the factors influencing these perceptions. A quantitative approach was employed using a descriptive research design. The results indicate that the Grade XI students' perception of the varied teaching methods in the Al-Qur’an Hadist subject at MA Negeri Kotabaru falls into the "high" category, with a score of 3,520. Factors influencing these perceptions include teacher strategies and creativity, clarity in material delivery, mastery of teaching methods, the use of instructional media and tools, and the learning environment. The findings demonstrate that the students' perceptions of the varied teaching methods in the Al-Qur’an Hadist subject align with the influence of the identified factors.   Keywords: Al-Qur’an Hadist, Varied Teaching Methods, Perception